One-Year Comparison of Efficacy and Safety of PreserFlo MicroShunt with Mitomycin C Applied by Sub-Tenon Injection Versus Sponge - Nora Majtanova; Adriana Takacova; Veronika Kurilova; Libor Hejsek; Juraj Majtan; Petr Kolar (Ophthalmology and Therapy)
Abstract Introduction This study was performed to compare the efficacy and safety of PreserFlo MicroShunt (PMS) implantation with mitomycin C (MMC) applied by sub-tenon injection versus conventional application by MMC-soaked sponges. Methods This retrospective, 1-year cohort study included 100 eyes of 100 patients with glaucoma who underwent PMS implantation with MMC (0.4 mg/ml) delivered either by sub-tenon injection (50 eyes) or via soaked sponges (50 eyes). The primary outcome measure at 1 year was intraocular pressure (IOP) reduction, with complete success defined as an IOP reduction of ≥ 20% and achieving a target IOP of ≤ 21 or 18 mmHg without the use of medication. Secondary outcomes, including corneal endothelial cell density (CECD) loss, the number of medications, and complications, were assessed and compared between the groups. Results Sustained reductions in mean IOP were observed in both groups over the 1-year follow-up, with no significant differences between the groups. The complete success rate, with a target IOP of ≤ 21 mmHg after 1 year, was 19.3% in the sponge group and 26.4% in the injection group. The qualified success rate was 59.0% and 87.4% in the sponge and injection groups, respectively. A longer survival rate was observed in the injection group than in the sponge group when IOP was below 21 mmHg. The mean CECD significantly decreased (P < 0.01) from baseline to each postoperative follow-up time point in both groups. At 1 year postoperatively, the percentage of total CECD loss was 8.1% in the sponge group and 8.0% in the injection group. However, no significant differences in mean CECD values, the number of medications, or adverse events were found between the groups. Conclusions PMS implantation with sub-tenon injection of MMC was comparable in terms of efficacy and safety to traditional MMC delivery via soaked sponges. However, the injection group demonstrated a significantly higher success rate than the sponge group.